A2_5 Deck the Halls - Bradley-Evans, Ryan; Gafur, Razzia; Heath, Ryan; Hough, Matthew (Physics Special Topics, 2017)
Physics often stretches the limits of what is physically possible for entertainment purposes. By applying known physics to these scenarios we often get unrealistic answers. From the 2006 movie “Deck the Halls”, we calculated how bright a house would have to be to be seen by people on the International Space Station (ISS). We find that the house would need to be at least 10.6×10^3 lm; the equivilent of 2638 LED Christmas lights.